Representation of Anxiety and Hope in Novel Beauty Is a Wound and Implementation in Indonesian Language Learning - Khairatunnisa Khairatunnisa (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research was motivated by the use of media in learning. The purpose of this study was to describe anxiety in the novel Women's Room by Agus Subakir and Beauty is Wounded by Eka Kurniawan in terms of form, causes, and implementation in Indonesian language learning. The research method used is descriptive qualitative research method, with a literature review approach. The data sources of this research are in the form of words, phrases, and sentences related to the implementation of Indonesian language learning contained in the two novels. Data collection techniques used reading and note-taking techniques. The results of this study indicate that both novels emphasize the desire to gain a sense of security, get out of anxiety, and find peace. Likewise with the implementation of Indonesian language learning which expects a conducive learning situation so that students feel safe and comfortable with the way the teacher does learning in class.